(untitled) (Journal of the College of Basic Education, 2022)
This study falls within a series of studies presented by the researcher on Islamic poetry, Al-KhassThe first Islamic trio.The researcher found that modernity is based on mutual satire, within this axisThe third. It has led to the dominance of specific vocabulary in spelling. Although it is not the most thuggish ofSemantic and technical aspects. It seems that its use, including the word meanness, was governedWith its rise to one of the opposing parties, and then this led to its circulation in a way that might beIt indicates an exaggeration at times, a failure to advance the technical significance of the term at other times, and a discrepancy.Whenever the abilities of the first three-thirds of Islam are drawn, when it comes from one of its parties, he is the factor